Peranan Pancasila Sebagai Ideologi Perekat Keutuhan Negara Kesatuan Republik Indonesia Diera Industri 5.0 - Nopal Gustin; M.Leri Laspigo; Paten Nuri; Rian Setiawan; M.Iqbal Anugrah (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Pancasila is the ideology of the Indonesian nation whose values can be a reference for the development of the nation's character to face the development of society 5.0 era. This study aims to measure the readiness of the younger generation in facing technological developments in the era of industrial revolution 5.0 and how the influence of Pancasila in the life of the nation. This study uses a mixed method, in addition to using a conceptual approach, it also uses a survey method by distributing questionnaires to obtain strong data. Conceptually, this research looks at and explores reference sources from books and journals that contain substance about character building based on Pancasila. Meanwhile, quantitative data were obtained from a survey conducted on a number of respondents who were students considered to have a high level of idealism. The problem studied in this study is the values contained in Pancasila to built a society character to face the era of society 5.0. The results show that Pancasila education plays a very important role in character building in this country, but political life has not supported the creation of the Pancasilaist character of the Society.